The effect of giving goat manure on lettuce growth and product by using yard land in Dulolong Village, Alor District - Andri Permata Timung; Nurkijah Bara; Ferdinan Demang (Agrovigor, 2023)
Goat manure is an organic fertilizer derived from goat manure which contains nutrients that are beneficial for plant growth and development. The purpose of this research was to (1) determine the effect of organic goat manure on the growth and yield of lettuce with the use of yardland. (2) Knowing the best dosage of goat manure organic fertilizer in increasing growth and yield of lettuce by utilizing Yard. This study was designed using a randomized block design (RBD) with 6 treatments and 3 replications so that there were 18 experimental units. K1: Without treatment (Control) K2: fertilizer as much as 5 tons.ha-1 K3: fertilizer as much as 10 tons.ha-1 K4: fertilizer as much as 15 tons.ha-1 K5: fertilizer as much as 20 tons.ha-1 K6: fertilizer as much as 25 ton.ha-1. To determine the effect of green manure using analysis of variance, if it is influential then continue using the Least Significant Difference test (LSD). The results showed that: (1) Dosing treatment of goat manure affected the growth of lettuce (plant height and the number of leaves) at the age of 1 MST, 2 MST, 3 MST, 4 MST, and 5 MST. However, it had no significant effect on the growth of the day after tomorrow at the age of 1 MST, 2 MST, 3 MST, 4 MST, and 5 MST, (2) Giving organic goat manure by 15 tons ha-1 gave the best effect in increasing lettuce production.